Tackling Conflicts of Interest: Policy Instruments in Different Settings. (2nd January 2016) - Ochoa, Rolando; Graycar, Adam
Abstract : Corruption affects and even shapes public policy in both developing and developed countries. Prevention of the form of corruption known as conflict of interest is one of the most challenging tasks for governments and the international community. This theory-driven article provides a framework of policy instruments and explores mechanisms from two areas of the world where conflict of interest is an important issue: Asia and Latin America. It argues that the creation of effective mechanisms to prevent and prosecute conflict of interest depends on the adequate operationalization of governance and social-control instruments that can regulate conflicts of interest.